The larva of Athripsodes genei (Rambur 1842) (Trichoptera, Leptoceridae) - Waringer, Johann; Graf, Wolfram (Zootaxa, 2014)
This paper describes the previously unknown larva of Athripsodes genei (Rambur 1842). Information on the morphology of the 5th larval instar is given and the most important diagnostic features are illustrated. In the context of existing identification keys the larva of A. genei keys together with A. albifrons (Linnaeus 1758), A. commutatus (Rostock 1874), A. leucophaeus (Rambur 1842) and Athripsodes tavaresi (Navás 1916). These species differ in the number of ventral edge setae at the 1st tibia and in the shape and colour of the submentum. With respect to zoogeography, Athripsodes genei is a (micro-)endemic of the collin and planar regions of Sardinia and Corsica (Graf et al. 2008). According to mandible morphology, A. genei is a collector-gatherer, shredder and, to a minor extent, also a predator.